What's in a name? Experimental evidence of the coup taboo. Issue 7 (3rd October 2022) - Grewal, Sharan; Kinney, Drew Holland
ABSTRACT: Leaders of military coups routinely deny that their actions amount to a coup, often labelling them as revolutions or even constitutional successions. These attempts to muddy the waters occasionally succeed in prompting discussions over whether the military's actions truly amount to a coup. But does the label matter? Does public support for military intervention decrease when it is labelled a coup? If so, how large is this "coup taboo"? In this article, we provide the first empirical evidence of the coup taboo across three large-scale survey experiments in Egypt, Algeria, and Tunisia. Across all three countries, we find that the coup taboo is substantial, with support for the military hypothetically removing the president falling by 15–50 percentage points when labelled as a coup. These results underscore the importance of labels, and suggest that anti-coup norms may be superficial, decreasing support for military interventions only when labelled as coups.